Comparing individual and peer education on the constructs of theory of planned behavior in mammography - Maryam Molaei-Zardanjani; Mitra Savabi-Esfahani; Fariba Taleghani (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Breast cancer is the most common cancer in women. It can be diagnosed in the first stage by screening. One of the methods for screening breast cancer is mammography. Mammography as a health behavior needs education. The theory of planned behavior examines the factors associated with the behavior. AIM: This research was conducted to compare the individual and peer education on the constructs of the theory of planned behavior in mammography. METHODS: This study was a clinical trial. A total of 100 women who attending the selected health centers of Isfahan city were classified randomly into two groups: peer and individual education. Education was based on the constructs of the theory of planned behavior (attitude relative to the mammography behavior, subjective norms, perceived behavioral control, and behavioral intention). The data were collected using a researcher-made questionnaire. Data were analyzed using descriptive-analytical statistics. RESULTS: The mean score of attitude toward behavior in the individual education group was significantly higher than peer education (P < 0.05). In addition, the average score of subjective norms in peer education group was significantly higher than individual education (P < 0.05). The mean scores of perceived behavioral control constructs and behavioral intention were not significantly different (P > 0.05). DISCUSSION: The results of this study showed the effectiveness of education (individual and peer) based on the theory of planned behavior on attitude toward behavior, subjective norms, perceived behavioral control, and behavioral intention related to performing mammography in women. It seems that using educational intervention can be useful to promote the screening behaviors of breast cancer. In general, there were no significant differences between the two methods in changing theoretical constructs.